Digital Marketing Strategy and Purchase Intention: A 7P Marketing Mix Approach to Enhancing Sales Performance of Bang Zack’s Chips MSME - Deby Nofriansyah; Muhammad Irwan Padli Nasution; Nurbaiti Nurbaiti (Jurnal Wacana Ekonomi, 2026)
The rapid growth of digital technology has fundamentally changed consumer purchasing behavior in the Indonesian snack food industry, creating both opportunities and challenges for micro, small, and medium enterprises (MSMEs). This study aims to analyze the implementation of digital marketing strategies based on the 7P Marketing Mix framework (Booms & Bitner, 1981) and its impact on purchase intention and sales performance of Kripik Bang Zack, an MSME producing chips. This study uses a qualitative descriptive method with in-depth interviews with 5 key informants, consisting of the business owner, 2 employees, and 2 loyal customers, selected through purposive sampling. Data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The findings show three main contributions: (1) Instagram and TikTok-based content marketing, as the most influential digital strategy, drove an approximately 73% increase in online sales over 12 months (from 300 to 520 units/month); (2) active customer engagement through social media strengthened brand loyalty and extended market reach beyond the local area, as evidenced by a growing proportion of non-local buyers; and (3) the integrated application of all 7P elements particularly the Promotion and Process dimensions was identified as the most critical factor in sustaining purchase intention among digitally active consumers. This study contributes to the limited literature on the implementation of digital marketing among Indonesian food MSMEs, offering a replicable strategic framework for similar small businesses looking to improve their digital sales performance.